2000
DOI: 10.1073/pnas.97.16.9026
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of the HIV gp120-CD4 binding reaction

Abstract: HIV infection is initiated by the selective interaction between the cellular receptor CD4 and gp120, the external envelope glycoprotein of the virus. We used analytical ultracentrifugation, titration calorimetry, and surface plasmon resonance biosensor analysis to characterize the assembly state, thermodynamics, and kinetics of the CD4-gp120 interaction. The binding thermodynamics were of unexpected magnitude; changes in enthalpy, entropy, and heat capacity greatly exceeded those described for typical proteinp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
373
2
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(425 citation statements)
references
References 41 publications
44
373
2
5
Order By: Relevance
“…Notably, the interaction of BMS-806 with gp120 was characterized by a binding enthalpy of Ϫ3.4 Ϯ 0.5 kcal͞mol (1 cal ϭ 4.18 J) and a binding entropy of 22 Ϯ 2 cal͞(K ϫ mol). The thermodynamics of BMS-806 binding to gp120 contrasts with the extremely large enthalpy and entropy changes associated with the binding of sCD4 or even CD4 miniproteins (30). The large negative entropy (approximately Ϫ167 cal͞(K ϫ mol) associated with the binding of soluble CD4 (sCD4) has been related to the significant structuring of gp120 residues that is necessary for the formation of the chemokine receptor-binding site (30).…”
Section: The Antiviral Activity Of Bms-806 Is Not Due To Inhibition Omentioning
confidence: 93%
See 2 more Smart Citations
“…Notably, the interaction of BMS-806 with gp120 was characterized by a binding enthalpy of Ϫ3.4 Ϯ 0.5 kcal͞mol (1 cal ϭ 4.18 J) and a binding entropy of 22 Ϯ 2 cal͞(K ϫ mol). The thermodynamics of BMS-806 binding to gp120 contrasts with the extremely large enthalpy and entropy changes associated with the binding of sCD4 or even CD4 miniproteins (30). The large negative entropy (approximately Ϫ167 cal͞(K ϫ mol) associated with the binding of soluble CD4 (sCD4) has been related to the significant structuring of gp120 residues that is necessary for the formation of the chemokine receptor-binding site (30).…”
Section: The Antiviral Activity Of Bms-806 Is Not Due To Inhibition Omentioning
confidence: 93%
“…The thermodynamics of BMS-806 binding to gp120 contrasts with the extremely large enthalpy and entropy changes associated with the binding of sCD4 or even CD4 miniproteins (30). The large negative entropy (approximately Ϫ167 cal͞(K ϫ mol) associated with the binding of soluble CD4 (sCD4) has been related to the significant structuring of gp120 residues that is necessary for the formation of the chemokine receptor-binding site (30). Apparently, BMS-806 does not induce such a large structuring of gp120; the measured entropy change resembles that of small hydrophobic molecules.…”
Section: The Antiviral Activity Of Bms-806 Is Not Due To Inhibition Omentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, sCD4 has been reported to bind to envelope proteins, including IIIB gp120, with K D values of 22 to 35 nM (12,59,88). Another study reported K D values in the range of 2.2 to 16 nM for a range of anti-CD4bs Fab fragments (including Fab b12) to MN gp120 (62).…”
Section: Fig 2 Vhh and Mab B12 Icmentioning
confidence: 99%
“…However, there were notable outliers, and these peptides stimulated T cells more efficiently than would be predicted from the measured TCRpMHC half-lives. Krogsgaard et al (26) also found that increases in a second parameter, change in heat capacity upon binding, which is often a measure of changes in conformation (27)(28)(29)(30), correlated with the stimulatory ability of the anomalous ligands. Specifically, when T cell stimulation potency was graphed as a function of the product of half-life (measured using soluble molecules) and change in specific heat capacity upon TCRpMHC binding, a good fit to all of the data were obtained.…”
mentioning
confidence: 99%